Innovative university as subject of network communication - Raisa A. Zayakina; Mark V. Romm (Высшее образование в России)
The article discusses the problems of effectiveness of established network relations and communication in tertiary education are discussed. The university’s role in academic and professional network functioning is analyzed in detail. There are given the recommendationsfor a university to become effective as a network actor as well as a subject of training specialists representing integrated professionally oriented educational product.